Bahasa Tansi in Use: At and Outside Home - Putri, Yulia Fransiska; Arianto, Muhammad Affandi (Universitas Negeri Padang, 2024)
Language use refers to the way speakers of a language use their language in different situations and contexts, including variations in written and spoken language. This research aimed to explore the dynamics of Bahasa Tansi use by the Sawahlunto community. It focused not only on language use at and outside but also on language use by children and the younger generation, as well as the language attitudes of the Sawahlunto people towards Bahasa Tansi. The research used a descriptive approach with data collection methods including Swadesh lists, questionnaires, and interviews with native Tansi speakers in Tansi Baru and Sikalang Village. The results showed that based on the lexical and phonological analysis of the Swadesh list, Bahasa Tansi was classified as a creole and was still not strong enough to be categorized as a language. These findings were derived from a comparative analysis of 206 words from the Swadesh list comparing Minangkabau and Bahasa Tansi. To this day, Bahasa Tansi is still used by the people of Sawahlunto in daily communication, with questionnaire results showing 86.8%. The community's positive attitude towards Tansi was also reflected in the questionnaire results, reaching 94%.